Architectural transformations of the buildings on estate at Rybna 5 street in Lublin - Janus, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The paper represents possible phaze transformations of buildings inn parcel at Rybna 5. The basis for analysis was architectural study group of buildings in 2011. The main goal of the research was to specify degree of preserve monument’s substance of the tenement as well as state of transformations phaze.